Engineered Spirituality in Bābīyah and Bahā’īyah: A Critical Study of Al-Dakhīl in Qur’anic Exegesis - Qohi, Abdullah; Ahmad, Nur Fatih; Mansur, Ahmad (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
This study investigates the hermeneutical strategies of the Bābīyah and Bahā’īyah, focusing on their symbolic and esoteric reinterpretations of the Qurʾān in legitimizing new religious authority. Employing a qualitative library-based approach, the research examines primary texts alongside classical tafsīr traditions and modern hermeneutical theories. The analysis demonstrates that the Bābīyah and Bahā’īyah shifted from the linguistic-philological hermeneutics of classical mufassirūn such as al-Ṭabarī, Ibn Kathīr, and al-Dhahabī toward charismatic-symbolic readings, where the authority of the interpreter overrides transmitted knowledge. Comparative engagement with contemporary hermeneutical models, including Nasr Hamid Abu Zayd’s cultural-linguistic paradigm, Abdullah Saeed’s contextualist approach, and Sahiron Syamsuddin’s maʿnā-cum-maghzā method, highlights both divergences and resonances. The study concludes that al-Dakhīl fī al-Tafsīr should not merely be viewed as deviation, but as a distinct hermeneutical logic mobilized in constructing theological legitimacy and communal identity.